Pengembangan Buku Pedoman Bermain Sains Anak Usia Dini Pada Pratama Widyalaya Berwawasan Tri Pramana - Aryana, I Made Putra; Wijaya, I Komang Wisnu Budi; Wiranata, I Gusti Lanang Agung; Supadmini, Ni Kadek; Hana, Nina D (UNIB Press, 2025)
Science learning for early childhood, especially in Pratama Widyalaya educational units, has not been optimal and has not been infused with Hindu values. This research aims to produce a science play guidebook for early childhood at the Pratama Widyalaya level with a Tri Pramana insight. This research is classified as development research using the 4D model consisting of define, which is the analysis of existing needs and problems, design, which is the design stage of the product to be developed, develop, which is the implementation stage of the design that has been made, and disseminate, which is the stage of disseminating the developed product to users. This research instrument uses expert validation sheets and practicality sheets. The data were analyzed descriptively. The results of the study stated that the science play guidebook for early childhood at the Pratama Widyalaya level with a Tri Pramana insight meets the valid criteria, namely a CVI of 0.87 and the practicality test results in scores ranging from 2.93 to 3.00 so that it is suitable for use in science learning in Pratama Widyalaya educational units.